THE EFFECT OF SOLVABILITY RATIO AND CURRENT RATIO ON PROFITABILITY AT CHEMICAL SECTOR COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE - Afriza Amir; Beatrice Wuu (JEBIM Prima, 2020)
Indonesia as a developing country has experienced quite rapid development in several industrial sectors, especially in the plastic and packaging sectors, metals and components, ceramics, glass and wood porcelain, chemicals, pet food, paper and cement. In general, companies that are established by individuals or groups have a goal that is to obtain optimal profits with minimal costs, to achieve these goals, good and reliable management is needed to be able to manage the company so that production resources become more effective and efficient. Management that is not good will lead to various obstacles that have a bad impact. The study concluded that the Debt To Asset Ratio had no effect and was not significant, Working Capital has a positive and significant , Current Ratio has no effect and is not significant on Profitability.. Debt To Asset Ratio, Working Capital, Current Ratio has a positive and significant effect simultaneously